The antioxidant N-acetylcysteine prevents accelerated atherosclerosis in uremic apolipoprotein E knockout mice - Ivanovski, Ognen; Szumilak, Dorota; Nguyen-Khoa, Thao; Ruellan, Nadya; Phan, Olivier; Lacour, Bernard; Descamps-Latscha, Béatrice; Drüeke, Tilman B; Massy, Ziad A (Elsevier BV, 2005)
Cardiovascular disease is the most frequent cause of mortality in chronic renal failure (CRF). Therefore, it is important to identify appropriate treatment measures. The antioxidant N-acetylcysteine (NAC) has been shown to reduce cardiovascular events in hemodialysis patients. Here we examine a possible direct effect of NAC supplementation on uremia-enhanced atherosclerosis in apolipoprotein E-deficient (apoE(-/-)) mice.